Building habit strength: A pilot intervention designed to improve food-safety behavior - Mullan, Barbara; Allom, Vanessa; Fayn, K.; Johnston, I. (Elsevier, 2014)
The purpose of this study was to firstly design an intervention to decrease cross-contamination in the home by the development of the habitual behavior of microwaving the dishcloth/sponge and secondly to determine if this behavior could be maintained over time. Participants were randomly assigned to either a high-frequency or low-frequency reminder habit building condition or a control condition. Results indicated that for both habit building conditions, food-safety behavior significantly increased compared to the control group and these changes were maintained at follow-up. Additionally, improvement in behavior was mediated by anincrease in habit strength. The major conclusion of this study is that providing a cue to action and reminders builds food-safety habits that result in changes in food-safety behaviors. This has major implications for other food-safety interventions.